ÁDEBIYATTANÍWDA KÓRKEM PSIXOLOGIZM TERMINI - Joldasbaeva, Biybixadisha Tlepbaevna (SCIENCE and SOCIETY, 2026)
The article examines the origin of the concept of artistic psychologism and the issues related to its formation as a literary term from the perspectives of world, Uzbek, and Karakalpak literary studies. The fact that the definitions of artistic psychologism proposed to date have remained largely empirical in nature and have failed to reveal its precise terminological meaning has led to various scholarly debates and discussions. This article may contribute to the systematization of these controversial issues and to the clarification of the terminological meaning of artistic psychologism.